PERAN GURU DALAM MEWUJUDKAN MADRASAH BERPRESTASI DI MAN 1 PONTIANAK - Saumi Setyaningrum (AL-ASASIYYA: Journal Of Basic Education, 2017)
This article, aims to explain the role of teachers in realizing achieving madrasah. This is raised, because madrassas in general, especially MAN 1 Pontianak is seen as a less competitive madrasah. In accordance with the vision of MAN 1 Pontianak namely: creating a generation of religious and achievement. To realize the vision of achievement, MAN 1 Pontianak rely more on extracurricular field with the reason students' ability in the academic field is still relatively low. To boost student achievement MAN 1 Pontianak revive all extracurricular activities. Teachers as the forefront of education and as a successful engineering designer of students as well as coaches in the field of extracurricular should be able to develop talents, interests and potential students. Extracurricular in MAN 1 Pontianak are: drum band, KIR, scout, paskibra, PMR, nasyid, dance, qosidah, religious Frisma, recitations, karate, voly, futsal, mathematics, physics, chemistry, biology, geography, economy, English, Arabic, band, rocket, LCC Constitution and theater. The role of the teacher as an extracurricular coach is in addition to being the main planner of extracurricular activities but also as a mentor, educator, trainer, innovator, advisor, creativity booster, evaluator and also a model for all learners. Achievements that have been generated from the extracurricular field include: the publication of 18 books by KIR extracurricular members. Extracurricular activities carried out in MAN 1 Pontianak has managed to make MAN I Pontianak known in the city of Pontianak and West Kalimantan Province.